Conventional and High-Sensitivity Malaria Rapid Diagnostic Test Performance in 2 Transmission Settings: Haiti 2017. (21st October 2019) - Rogier, Eric; Hamre, Karen E S; Joseph, Vena; Plucinski, Mateusz M; Presume, Jacquelin; Romilus, Ithamare; Mondelus, Gina; Elisme, Tamara; van den Hoogen, Lotus; Lemoine, Jean Frantz; Drakeley, Chris; Ashton, Ruth A; et al.
Abstract: Accurate malaria diagnosis is foundational for control and elimination, and Haiti relies on histidine-rich protein 2 (HRP2)–based rapid diagnostic tests (RDTs) identifying Plasmodium falciparum in clinical and community settings. In 2017, 1 household and 2 easy-access group surveys tested all participants (N = 32 506) by conventional and high-sensitivity RDTs. A subset of blood samples (n = 1154) was laboratory tested for HRP2 by bead-based immunoassay and for P. falciparum 18S rDNA by photo-induced electron transfer polymerase chain reaction. Both RDT types detected low concentrations of HRP2 with sensitivity estimates between 2.6 ng/mL and 14.6 ng/mL. Compared to the predicate HRP2 laboratory assay, RDT sensitivity ranged from 86.3% to 96.0% between tests and settings, and specificity from 90.0% to 99.6%. In the household survey, the high-sensitivity RDT provided a significantly higher number of positive tests, but this represented a very small proportion (<0.2%) of all participants. These data show that a high-sensitivity RDT may have limited utility in a malaria elimination setting like Haiti.